Environmental conflict - Clarke, Tracylee. (SAGE Publications, Inc, 2016)
Environmental Conflict Management introduces students to the research and practice of environmental conflict and provides a step-by-step process for engaging stakeholders and other interested parties in the management of environmental disputes